1986
DOI: 10.1093/ajcn/44.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Eating behavior and plasma beta-endorphin in bulimia

Abstract: To study the possible role of plasma beta-endorphin in bulimia, we measured plasma beta-endorphin immunoreactivity in 34 female patients with normal-weight bulimia and 34 normal female controls matched for weight as percent of ideal. Plasma beta-endorphin immunoreactivity in bulimics (mean 59.6 pg/ml; SEM 5.6) was significantly lower (p less than 0.05) than in controls (mean 79.5 pg/ml; SEM 8.5). Within the bulimic group, plasma beta-endorphin immunoreactivity correlated inversely with severity of bulimic symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 15 publications
0
16
1
1
Order By: Relevance
“…In plasma, β-EP concentrations were found to be lower than normal in one study (Waller et al, 1986) but higher in another one (Fullerton, Swift, Getto, & Carlson, 1986).…”
Section: Opioid Peptidesmentioning
confidence: 74%
See 1 more Smart Citation
“…In plasma, β-EP concentrations were found to be lower than normal in one study (Waller et al, 1986) but higher in another one (Fullerton, Swift, Getto, & Carlson, 1986).…”
Section: Opioid Peptidesmentioning
confidence: 74%
“…Corticotropin-releasing hormone (CRH) Gwirtsman et al (1983), Hotta et al (1986), Krahn and Gosnell (1989) Kaye et al (1982Kaye et al ( , 1987, , Waller et al (1986) Fullerton et al (1986, Baranowska (1990), Lesem et al (1991), Brambilla et al (1991), Brewerton et al (1992) CSF dynorphins Gerner and Yamada (1982), Kaye et al (1988), Pirke et al (1993), Baranowska et al (2000) Plasma SRIF ↓↑ → Plasma SRIF (response to test meal) ↑ Thyrotropin-releasing hormone (TRH) Devlin et al (1990), Lesem et al (1994) Gold et al (1983), Demitrack et al (1992), Chiodera et al (1993), Frank et al (2000) …”
Section: Central Peptides Modulating Eating Behaviour and Energy Homementioning
confidence: 99%
“…Also, sweet cravings and subsequent excessive consumption of a large amount of palatable food are frequently reported by opiate drug abusers (Weiss 1982;Morabia et al 1989). Furthermore, naloxone has been found e¤ective, to some degree, in treatment of bulimia, a condition characterized by uncontrolled ingestion of palatable food (Waller et al 1986;Jonas and Gold 1987;Brewerton et al 1992). Additionally, naloxone reduces the taste preferences for highly palatable foods in binge eaters and control subjects (Drewnowski et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Fullerton et al [8] showed P-endorphin levels higher than normal during morning hours. However, in this study bulimic patients had taken 100 g oral glucose at 09.00 h, which might have modified the P-endorphin-secretory pattern, as glucose is a P-endorphin-relcasing factor [9], In con trast, Waller et al [10] found reduced (3-endorphin con centrations in single blood samples taken at 10.00 h from bulimic women.…”
Section: Introductionmentioning
confidence: 73%